A review of heritage artwork in Malaysia from the financial reporting perspective - Fauzi, Nuruu Ain; Rosli, Mohamad Hafiz (International Journal of Accounting, Finance and Business, 2025)
Heritage artwork represents a unique class of public assets that embody cultural identity, historical continuity, and artistic value. However, it remains difficult to report and value from a financial reporting perspective due to the absence of active markets and standardised measurement approaches. This review paper aims to synthesise existing research on heritage artworks in Malaysia, identify persistent challenges, and suggest directions for future studies. A systematic review of relevant academic articles from the Google Scholar databases was conducted and analysed using a thematic approach. The findings reveal four dominant themes that continue to shape heritage artwork reporting practices in Malaysia: (1) Reporting and Disclosure, (2) Valuation Challenges, (3) Standards and Frameworks, and (4) Market Evidence and Global Context. The absence of a comprehensive national heritage and art market database further weakens valuation credibility and comparability across agencies. This study contributes to the growing body of literature on heritage asset accounting by offering an integrated synthesis of Malaysian and international perspectives. It highlights the need for structured disclosure frameworks, hybrid valuation models, and stronger institutional collaboration between cultural and financial authorities. Furthermore, it provides practical insights for policymakers to formulate clear reporting guidelines, enhance professional training, and establish a systematic market database for heritage artworks. These efforts are essential to promote transparency, accountability, and sustainable heritage management within Malaysia’s public sector financial reporting.